Redefining Exclusivity : How Luxury Brands Use Storytelling to Adapt to the Digital and Experiential Economy - Knigge, Marie Joana (2025)
The general objective of this thesis is to explore the role of storytelling in the luxury jewellery and watches segment. Specifically, how storytelling functions as a strategic tool by examining key challenges, the role of storytelling, evolving digital tools and techniques, and anticipated consumer trends, to understand how brands preserve exclusivity while adapting to a changing market landscape. The study draws on qualitative data through expert interviews and observations of storytelling campaigns. Results of the research highlight the multifaceted notion of storytelling in the hard luxury segment, with a strong emphasis on emotional engagement, authenticity, and the integration of digital tools. The interviews highlight the importance of adapting to evolving consumer expectations through carefully curating brand narratives to remain relevant, create emotional resonance, and cultivate the exclusive appeal of these brands.